Development of a model of dementia support and pathway for culturally and linguistically diverse communities using co-creation and participatory action research. Issue 12 (7th December 2016) - Goeman, Dianne; King, Jordan; Koch, Susan
Abstract : Objective: To develop an inclusive model of culturally sensitive support, using a specialist dementia nurse (SDN), to assist people with dementia from culturally and linguistically diverse (CALD) communities and their carers to overcome barriers to accessing health and social care services. Design: Co-creation and participatory action research, based on reflection, data collection, interaction and feedback from participants and stakeholders. Setting: An SDN support model embedded within a home nursing service in Melbourne, Australia was implemented between October 2013 and October 2015. Participants: People experiencing memory loss or with a diagnosis of dementia from CALD backgrounds and their carers and family living in the community setting and expert stakeholders. Data collection and analysis: Reflections from the SDN on interactions with participants and expert stakeholder opinion informed the CALD dementia support model and pathway. Results: Interaction with 62 people living with memory loss or dementia from CALD backgrounds, carers or family members receiving support from the SDN and feedback from 13 expert stakeholders from community aged-care services, consumer advocacy organisations and ethnic community group representatives informed the development and refinement of the CALD dementia model of care and pathway. We delineate the three components of the 'SDN' model: the organisational support; a description of the role; and the competencies needed. Additionally, we provide an accompanying pathway for use by health professionals delivering care to consumers with dementia from CALD backgrounds. Conclusions: Our culturally sensitive model of dementia care and accompanying pathway allows for the tailoring of health and social support to assist people from CALD backgrounds, their carers and families to adjust to living with memory loss and remain living in the community as long as possible. The model and accompanying pathway also have the potential to be rolled out nationally for use by health professionals across a variety of health services.